Characteristics and publication patterns of obstetric studies registered in ClinicalTrials.gov. (14th November 2013) - Stockmann, Chris; Sherwin, Catherine M.T.; Koren, Gideon; Campbell, Sarah C.; Constance, Jonathan E.; Linakis, Matthew; Balch, Alfred; Varner, Michael W.; Spigarelli, Michael G.
Abstract Physiologic changes during pregnancy alter the pharmacokinetics, safety, and efficacy of many drugs. For clinicians, there is often uncertainty regarding the safety of these drugs due to a scarcity of published data. This study aimed to comprehensively evaluate the characteristics and publication patterns of obstetric studies registered in ClinicalTrials.gov from 2007 to 2012. Primary outcome measures, funding sources, inclusion criteria, and the reporting of study results were evaluated. A manual review of Medline/PubMed was performed to identify publications associated with studies registered in ClinicalTrials.gov. Of 93, 709 total studies, there were 5, 203 (6%) obstetric studies registered in ClinicalTrials.gov. Interventional studies accounted for 70% and 30% were observational. Clinical trials of drugs (49%), procedures (13%), and behavioral interventions (12%) were most common. Among interventional drug trials, 84% featured randomized allocation to study arms and 93% included measures of safety and/or efficacy as primary endpoints. Of 946 (18%) studies completed more than 2 years ago, only 11% had reported results and <7% had been published. In an area with a great need for evidence of safe and effective therapies, the low publication rate of completed studies incorporating elements of high‐quality trial design is concerning. The sources of this trend should be closely investigated.